# 9x+1-7x-18=3x+5

## Simple and best practice solution for 9x+1-7x-18=3x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 9x+1-7x-18=3x+5 equation:

Simplifying 9x + 1 + -7x + -18 = 3x + 5 Reorder the terms: 1 + -18 + 9x + -7x = 3x + 5 Combine like terms: 1 + -18 = -17 -17 + 9x + -7x = 3x + 5 Combine like terms: 9x + -7x = 2x -17 + 2x = 3x + 5 Reorder the terms: -17 + 2x = 5 + 3x Solving -17 + 2x = 5 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -17 + 2x + -3x = 5 + 3x + -3x Combine like terms: 2x + -3x = -1x -17 + -1x = 5 + 3x + -3x Combine like terms: 3x + -3x = 0 -17 + -1x = 5 + 0 -17 + -1x = 5 Add '17' to each side of the equation. -17 + 17 + -1x = 5 + 17 Combine like terms: -17 + 17 = 0 0 + -1x = 5 + 17 -1x = 5 + 17 Combine like terms: 5 + 17 = 22 -1x = 22 Divide each side by '-1'. x = -22 Simplifying x = -22

### See similar equations:

| 14x+3=7x-39 | | 39x+2.65=-31.68+42.03x | | 7-3(1x+2)+4x+40= | | 3t+8(2t-6)= | | 4x+5=65-2x | | 6x-4=-22 | | 3f+4-2f+6= | | 84-4x=8x+24 | | n-1.34=4 | | 9-3v=2v+54 | | 12m-14=130 | | -5x-5=9x-11 | | -5-5x=11-9x | | 5x+6=36 | | 131-5X=3X+11 | | 7+6x=3x+43 | | 6X+5=-60-7X | | -6.8=-0.9+r | | -158-9X=9X+22 | | 13-10X=53-17X | | 3y-3=6 | | 12x=6x+12 | | 3(x-2)=18 | | 139-2X=43X+19 | | 28=-2x+8 | | 6(x-2)=42 | | 4x=-2x+30 | | 4x=-3x+21 | | 9x-2=61 | | 2(x-4)=0 | | 6x-5=43 | | 5x+2-x=26 | | 6+2a=48 | | 19=4b+7 | | 4(y-6)=7y | | 3x+11=47 | | (5x+8)(-3x-2)= | | 7(w+1)=5(2w-3)+1 | | (x+4)+(-7x-6)= | | (5x+8)-(-3x-2)= | | 1x+1x+5x=68 | | 4c+12=7c+11.64 | | -8+10r=-128 | | 7x-24=5x+18 | | -3.4+0.7p=0.9p+5.3 | | 7X-8=66 | | 12X+6=8X+22 | | 2X+46=5X+10 | | 8X-19=2X+5 | | 4X+19=11X-65 | | 6X-1=15X-73 | | 2x+12=5x-15 | | 2+3X=18+X | | 7X-18=66 | | 6(18z+5)=x | | 3X+11=91-5X | | 109-5X=10X+19 | | 11x=6x+20 | | 5-5X=11-7X | | 5x-3=22 | | 4X+8=-104-10X | | -71-10X=8X+19 | | 7-9X=31-30X | | 4y-2(y-5)=2 | | 44-7X=2X+16 |